Translation as a novelty in the Colección de los Tratados, Convenios y documentos internacionales of the Marquis of Olivart - Castellano Martínez, José María (chronotopos – A Journal of Translation History, 2020)
This paper aims to highlight the relevance of the Colección de los Tratados, Convenios y documentos internacionales of the Marquis of Olivart from a translation history perspective. This international legal index covering the treaties and conventions held by the governments of Spain from the effective reign of Isabella II to the times of her grandchild Alphonse XIII was compiled between 1890 and 1912 in the Spanish Restoration context. After a brief social and historical introduction to this period, we have, with reference to Lepinette (1997), exposed the reasons that motivated this project–inspired by other national and foreign collections–, as well as analysed its structure and its process of compilation. Translation arises as the main novelty of this Spanish index –developed under royal auspices– through the incorporation of language versions, classified in four types. The collector’s concerns about the warranty of authenticity of the texts define translations as an essential instrument in order to avoid possible misinterpretations of other language versions. Because of this, linguistic equivalence arises next to legal equivalence when language versions of a same document are compared, revisiting legal veracity from a linguistic point of view. We conclude by sharing some considerations about these approaches that could contribute to translation history in the field of diplomacy.